200 years of diagnosis and treatment of cervical precancer. (December 2020) - Reich, Olaf; Pickel, Hellmuth
Abstract: Objectives: The history of the diagnosis and treatment of cervical precancer is fragmentary. Findings in the English-speaking and German-speaking areas vary considerably. We aim to describe the history of clinical advances in diagnosis and treatment of cervical precancer and identify areas where further work is required. Study design: We conducted a search of PubMed and Google Scholar. Full article texts were reviewed. Reference lists were screened for additional articles and books. 9 basic articles in German and 13 basic articles in books were identified. Results: The first images of the ectocervix were published by H. Lebert (1812–1879) in the middle of the nineteenth century. R. Meyer's (1864–1947) theory of erosions, which dominated cervical pathology in the nineteenth century, was later refuted in studies by C. A. Ruge (1846–1926) and J. Veit (1852–1917). In 1908 W. Schauenstein (1870–1943) recognized the step-by-step development of cervical cancer. H. Hinselmann (1884–1959) replaced the purely histopathological approach previously with the use of colposcopy. All conization methods applied today can be traced back to amputation of the ectocervix as first indicated by J. Marion Sims (1813–1883) in 1861. In 1928 M. N. Hyams was the first to describe an excision method that employed electrodiathermy. The method of cold knife conization is based on a publication by J.W. Scott from 1957. The final breakthrough to effective electrodiathermy was achieved with the publications of W. Prendiville. Conclusions: This paper is a step toward a better understanding of what we think and do today based on past findings of colposcopists and gynecopathologists.